The Weight Performance Stability of Mice on Modeling Obesity-Associated Hyperglycemia Induced by Dextrose Monohydrate - Deksa Yudha Syach Putra; Setiyo Budi Santoso; Heni Lutfiyati (Biology, Medicine, & Natural Product Chemistry, 2022)
Previously, streptozotocin and alloxan were employed to imitate hyperglycemia in mice. High doses of sucrose were also induced as an alternative. Due to body mass index has been associated with hyperglycemia, the evidence of weight body index in various induction alternate kinds, however, have not been fully reported. Here-in, we report on the weight performance stability of mice body weight induced by dextrose, streptozotocin, and alloxan. To begin, all mice were divided into six groups of five, with one reserve in each. Following seven days of acclimatization, the mice were induced for nine days of hyperglycemia modeling; alloxan (Groups A and D), streptozotocin (Group B and E), dextrose monohydrate (Groups C and F). On preclinical research animals modelling related to obesity-associated hyperglycemia in mice, dextrose monohydrate induction was most successful than streptozocotin and alloxan induction, which performed best during the induction period (31% weight growth) and after metformin intervention (36% weight growth). Overall, dextrose monohydrate is most suitable to be used for modeling type 2 diabetes mellitus test animals rather than alloxan and streptozocotin.